A case study on factors affecting tourism sector at Kelantan / Noor Hakimah Saleh - Saleh, Noor Hakimah (Faculty of Business and Management, 2013)
This study is conducted to identify the factor s for tourist arrival at Kelantan. On this research, Kelantan was chosen due to the limited research have been done about tourism in Kelantan. Kelantan is a destination for holiday especially for domestic tourist and foreigner. Indeed, the various factors have positioned Kelantan to reap the gains of the tourism industry as the country moves forward towards being a high-income economy by the year 2020.